2019
DOI: 10.1186/s12199-019-0761-4
|View full text |Cite
|
Sign up to set email alerts
|

Intra-individual variations of organophosphate pesticide metabolite concentrations in repeatedly collected urine samples from pregnant women in Japan

Abstract: BackgroundLow-dose exposure to organophosphate (OP) insecticides during pregnancy may adversely affect neurodevelopment in children. To evaluate the OP exposure levels, single urine sampling is commonly adopted to measure the levels of dialkylphosphates (DAPs), common OP metabolites. However, the inter-day variations of urinary DAP concentrations within subjects are supposed to be large due to the short biological half-lives of the metabolites, and it is thus considered difficult to accurately assess OP exposu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 24 publications
(32 reference statements)
1
7
0
Order By: Relevance
“…To the best of our knowledge, this is the first study to investigate urinary DAP concentrations of Japanese pregnant women on this scale. Urinary DAP concentrations were comparable with those in another Japanese study [ 21 ] and in previous studies from other countries [ 3 , 6 , 48 , 49 , 50 , 51 , 52 ]. In this study, strict QC measures were employed such as reproducibility, repeatability (intermediate precision), blank test, linearity of the calibration curves, duplicated measurements, recovery of IS samples, target ion/qualifier ion ratio and external QC.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…To the best of our knowledge, this is the first study to investigate urinary DAP concentrations of Japanese pregnant women on this scale. Urinary DAP concentrations were comparable with those in another Japanese study [ 21 ] and in previous studies from other countries [ 3 , 6 , 48 , 49 , 50 , 51 , 52 ]. In this study, strict QC measures were employed such as reproducibility, repeatability (intermediate precision), blank test, linearity of the calibration curves, duplicated measurements, recovery of IS samples, target ion/qualifier ion ratio and external QC.…”
Section: Discussionsupporting
confidence: 88%
“…Urinary metabolites of OPPs, i.e., DAPs, have short half-lives ranging from 2 to 15.5 h [ 17 , 18 ]. One study on Japanese pregnant women reported intra-class correlation coefficients (ICCs) to be 0.42–0.55 [ 21 ], while studies conducted in other countries provided −0.01–0.52 [ 51 , 56 , 57 , 58 ]. According to the rule of thumb, an ICC of 0.4 is categorised as “moderate” [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar studies have been carried out in different countries, so in comparison to these levels of DAP, they were slightly higher than the ones from the Columbia Center for Children’s Environmental Health, another NYC-based cohort [ 47 ]. These levels were lower than for most European and Asian cohorts [ 48 , 49 ]. Many authors tried to associate the increase of these levels of DAP with vegetable and meat intake.…”
Section: Resultsmentioning
confidence: 63%
“…While biomonitoring provides a rough estimate, it is often considered a more biologically accurate way of measuring OP exposure. Future studies should consider using the highly specific method of gas chromatography coupled with tandem mass spectrometry for biomonitoring [ 80 , 81 , 82 ].…”
Section: Discussionmentioning
confidence: 99%